2000
DOI: 10.1097/00000374-200011000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Binge Ethanol Consumption Causes Differential Brain Damage in Young Adolescent Rats Compared With Adult Rats

Abstract: The young-adolescent brain shows differential sensitivity to alcohol-induced brain damage compared with adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
1
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 43 publications
13
111
1
7
Order By: Relevance
“…To the extent that these data are applicable to humans, the results of the present study along with other research employing animal models of adolescence [e.g., 5,12,25,29,30,34,45,46] provide further evidence that adolescents may respond and adapt differently to repeated episodes of ethanol exposure than their more mature counterparts, with mechanisms underlying these adaptations also being age-specific. In addition to further characterizing adolescentspecific neurobehavioral alterations following repeated ethanol exposure, studies are needed to explore whether these adolescent-specific adaptations to and consequences of chronic ethanol might put them at higher risk for extensive alcohol use and the eventual emergence of alcohol abuse disorders.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…To the extent that these data are applicable to humans, the results of the present study along with other research employing animal models of adolescence [e.g., 5,12,25,29,30,34,45,46] provide further evidence that adolescents may respond and adapt differently to repeated episodes of ethanol exposure than their more mature counterparts, with mechanisms underlying these adaptations also being age-specific. In addition to further characterizing adolescentspecific neurobehavioral alterations following repeated ethanol exposure, studies are needed to explore whether these adolescent-specific adaptations to and consequences of chronic ethanol might put them at higher risk for extensive alcohol use and the eventual emergence of alcohol abuse disorders.…”
Section: Discussionsupporting
confidence: 60%
“…These brain regions are among those that undergo considerable remodeling during adolescence [1,15,16,18,35,37,48,49] and, hence are likely targets for contributing to the disruption in social preference following chronic adolescent exposure to ethanol. Indeed, there are a number of reports that ethanol-induced damage in these and other brain regions may be more pronounced during adolescence than in adulthood [5,22]. For instance, Crews et al [5] demonstrated that 4 days of "binge" exposure to high doses of ethanol (9-10 g/kg/day) produces cell death, which is more evident in adolescent than adult rats in a number of frontal-anterior brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies show greater sensitivity during adolescence to the effects of alcohol on spatial working memory (Little, et al, 1996;Silveri & Spear, 1998;Swartzwelder, et al, 1998;White et al, 2002;White, et al, 2000;Yttri, Burk, & Hunt, 2004), social facilitation (Varlinskaya & Spear, 2006), and long-term potentiation (Pyapali, et al, 1999;Swartzwelder, Wilson, & Tayyeb, 1995), as well as greater cortical damage (Crews, et al, 2000;Hollstedt, Olsson, & Rydberg, 1980;Little et al, 1996). In humans, hippocampal (De Bellis et al, 2000;Nagel, et al, 2005) and prefrontal (De Bellis et al, 2005) volumes appear smaller and brain response during spatial working memory is abnormal (Tapert et al, 2004) in adolescents with alcohol use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Brain regions adjacent to these major structures also will be available for analysis, and the Working Group anticipates that pathologists will follow the routine practice of evaluating entire sections rather than limiting the examination to the main features. The Working Group recognizes that different institutions vary with respect to evaluation of the rodent olfactory bulb for general toxicity screens but judges that this structure merits consideration for routine examination due to its importance as a potential target for inhaled (Colin-Barenque et al 1999) and ingested (Crews et al 2000) small molecule toxicants as well as a rich source of neural stem cells (Lennington, Yang, and Conover Midbrain, caudal X Pons X X X Pyramids X X X Cerebellum X Deep cerebellar nuclei X X X X Reticular formation X X Trigeminal nuclei and tracts X Medulla oblongata X X Choroid plexus Note: The table shows brain structures visible at given levels (using features visible when the organ is trimmed near the planes in Figure 1). Sections (from Figure 2) 1 2 3A 3B 4 5A 5B Brain structures (listed from rostral to caudal) X X X X Caudate/putamen X X X X X X Cerebral cortex (frontal, parietal, temporal, occipital) X X X Corpus callosum X Anterior commissure X Septal nuclei X X X Internal capsule X X X External capsule X X Hypothalamus X Amygdala X X X Thalamus X X Hippocampus X X Cerebral peduncles X Optic tract X Midbrain X Pons X Pyramids X Cerebellum X X Reticular formation X Trigeminal nuclei X Medulla oblongata X X X X X Choroid plexus Note: The table shows brain structures visible in given sections (using features visible when the organ is trimmed at the levels in Figure 2).…”
Section: Brain Trimmingmentioning
confidence: 99%